Training on Basic Digital Marketing and Business Mentality to Children of Mandhanisiwi Orphanage PKU Muhammadiyah Purbalingga - Alfalisyado; Muchammad Agung Miftahuddin; Edi Joko Setyadi (Journal of Society, Community and Business Development, 2024)
The program aims to create a strong and independent generation in terms of economy, creativity, mentality, and self-reliance through business motivation. In addition, this program also aimed to provide an open mindset in utilizing technology for positive and productive activities. This program was implemented by collaborating with partners in the Purbalingga district, namely Mandhanisiwi Orphanage PKU Muhammadiyah Purbalingga. Participants in this program were 47 orphanage children of junior high school (SMP) and senior high school (SMA) levels. The result of this program is an output in the form of increasing participants' knowledge about fostering the entrepreneurial spirit through the ease of technology by carrying Islamic values based on a solid mentality and giving a way to deal with situations that will occur when running a business, both independently and in groups.